Composition Color Space: Three Key Words in Art Design - Wang, Zhongheng (Transactions on Social Science, Education and Humanities Research, 2024)
As found in the practice of arts, which is the same as of sciences, a design without imagination is like the water running from nowhere and trees without roots, deprived of vitality and artistic appeal. As illustrated in the old saying that a thousand li journey is started by taking the first step, the three compositions work as both the foundation of art design and provider of unlimited imagination and creativity for urban design and city planning.